مؤشرات جداول حياة ذبابة القطن البيضاء Bemisia tabaci (Gennadius, 1889) على البندورة (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
Biology of Bemisia tabaci (Gennadius, 1889) was studied in laboratory, on tomato plants grown under conditions of 25 ± 1 ° C, 70 ± 2% RH and Photoperiod (14 L: 10 D) hours (light : darkness). The parameters were calculated using TwoSex-MSChart. Results showed the following values: net reproductive rate R0 = 31.89±4.32 Female / female / generation, the intrinsic rate of increase (r) = 0.1266±0.0052 Female / female / day, mean generation time (GT) = 27.343±0.23 days, (DT) = 5.473 days, gross reproductive rate (GRR) = 46.58±6.58 individuals / offspring, Survival rate (lx) = 0.9988, fecundity (F) = 66.78±3.055 eggs / female, total developmental times of immature mean= 22.75±0.084 days, Adult pre-oviposition period of female adult (APOP) = 0.22±0.0868, Mean length Adult female age = 33.22±0.36 days. The Mean age of the adult male is 32.04±0.37 days. Results of this study are useful to understand the Dynamic numbers in cotton whitefly. درست مؤشرات جداول حياة ذبابة القطن البيضاء Bemisia tabaci (Gennadius, 1889) مخبرياً، حيث ربيت على نباتات البندورة المزروعة ضمن أصص في ظروف مخبرية كانت درجة الحرارة 25±1 سْ ورطوبة نسبية 70±2% وفترة إضاءة D10:L14 ساعة (ضوء : ظلام)، وحسبت المؤشرات باستخدام برنامج TwoSex-MSChart، حيث أظهرت النتائج قيم المؤشرات التالية: معدل التعويض الصافي (R0)= 31.895±4.3217 أنثى/أنثى/جيل، معدل الزيادة الفعلية (r)= 0.1266±0.0052 أنثى/أنثى/يوم، مدة الجيل (GT)= 27.343±0.23 يوم، زمن التضاعف (DT)= 5.473 يوم، معدل الإنتاج (التكاثر) الإجمالي للإناث (GRR)=46.58±6.589 فرد/ذرية، معدل البقاء على قيد الحياة (lx)= 0.9988، الخصوبة (F)= 66.78±3.055 بيضة/أنثى، معدل  تطور الأطوار غير الكاملة 22.75±0.084 يوماً، معدل مدة ما قبل وضع البيض للإناث (APOP)= 0.22±0.0868، متوسط طول عمر البالغة الأنثى= 33.22±0.36 يوماً، متوسط طول عمر الذكر البالغ 32.04±0.37 يوماً، تفيدنا هذه الدراسة في فهم تغير أعداد ذبابة القطن البيضاء.